Irregularities in the canonical trial sued against Jon of Arc, the Maid of France (January-may 1431) - LE TOURNEAU, DOMINIQUE (Prawo Kanoniczne, 2017)
As shown by the trial which declared in 1456 the nullity of the sentence of death pronounced against Joan of Arc 25 years before, the first trial was tangled with numerous canonical irregularities. The article first deals with the prerequisites of the trial, the conditions of the arrest of Joan of Arc, of detention in an English jail in an inhuman way, and the non respect of the norms related to a trial which was supposed to be a religious one, that is to say against somebody accused of heresy, schism, idolatry, witchcraft and of being relapse. Then the author describes the unfolding of the trial, highlighting one by one the vices and defaults of the former sentence, as well as the masquerade of abjuration in Saint-Ouen, in the city of Rouen. For the Great Inquisitor of France, the sentence of 1431 was null for six reasons: 1) incompetence of judges, for default of juridiction on part of Cauchon, Bishop of Beauvais. — 2) obvious malicious intent and partiality of Cauchon. — 3) the fact that the sentence was pronounced after challenge and appeal. — 4) falsification of the acts. — 5) suspicions which was taken as basis of the trial. — 6) obvious iniquity and et intolerable error of the sentence.